After Empire : Scott, Naipaul, Rushdie. - Gorra, Michael (University of Chicago Press, 1997)
In After Empire Michael Gorra explores how three novelists of empirePaul Scott, V.S. Naipaul, and Salman Rushdiehave charted the perpetually drawn and perpetually blurred boundaries of identity left in the wake of British imperialism. Arguing against a model of cultural identity based on race, Gorra begins with Scott's portrait, in The Raj Quartet, of the character Hari Kumara seeming oxymoron, an "English boy with a dark brown skin," whose very existence undercuts the belief in an absolute distinction between England and India. He then turns to the opposed figures of Naipaul and.